Das Praxissemester als Ort religionspädagogischer Professionalisierung - Caruso, Carina; Hengesbach, Rudolf (SEMINAR – Lehrerbildung und Schule)

„Nein, ich war nicht beim Sport“ - Klingsieck, Katrin B.; Weigelt, Matthias (Zeitschrift für Sportpsychologie)
Zusammenfassung. Die Rolle von Prokrastination, dem unnötigen Aufschieben von intendierten Tätigkeiten wider besseren Wissens, ist bisher noch nicht für die Domäne Sport untersucht worden. Ziel dieses Beitrags ist es daher, den Zusammenhang zwischen Prokrastination und dem wöchentlichen Sporttreiben zu untersuchen. In einer Onlinestudie mit 167 Sportstudierenden (92 Frauen; Durchschnittsalter = 21 Jahre) wurden dazu die allgemeine sowie die sportspezifische Prokrastination in Relation zu den Persönlichkeitsvariablen Gewissenhaftigkeit und Neurotizismus, der volitionalen Variable Handlungskontrolle, der motivationalen Variable Selbstwirksamkeit im Sport sowie der Häufigkeit sportlicher Aktivitäten untersucht. Die Ergebnisse der Korrelations-, Regressions- und Mediationsanalysen zeigen, dass Prokrastination auch für sportliche Akvtivitäten ein ernst zu nehmendes Phänomen sein kann. Darüber hinaus ermutigen sie zur Entwicklung einer sportspezifischen Prokrastinationsskala.

On the Measurement of Procrastination: Comparing Two Scales in Six European Countries - Svartdal, Frode; Pfuhl, Gerit; Nordby, Kent; Foschi, Gioel; Klingsieck, Katrin B.; Rozental, Alexander; Carlbring, Per; Lindblom-Ylänne, Sari; Rębkowska, Kaja (Frontiers in Psychology)

Positive Auswirkungen (gesundheits-)psychologischer Ausbildungsinhalte im Studium auf die arbeitsbezogenen Belastungsmuster von Referendarinnen und Referendaren mit dem Unterrichtsfach Sport - Weigelt, M.; Lex, H.; Wunsch, K.; Kämpfe, A.; Klingsieck, Katrin B. (Sportunterricht)

Academic Procrastination: Psychological Antecedents Revisited - Steel, Piers; Klingsieck, Katrin B. (Australian Psychologist)

Grammatisches Lernen

Sprachgeschichtsforschung im Horizont von Nähe und Distanz - Tophinke, Doris (Zur Karriere von Nähe und Distanz)

Grammatisches Lernen (Basisartikel) - Feilke, Helmuth; Tophinke, Doris (Praxis Deutsch)

Graffiti. Formen, Traditionen, Perspektiven - Papenbrock, Martin; Tophinke, Doris (Sprache in der Kunstkommunikation)

"Es war einer dieser Nächte ..." Writer Storys zwischen Fiktionalität und Faktualität - Papenbrock, Martin; Tophinke, Doris (Der Deutschunterricht)

„In den tiefsten Winkeln unserer Betonwälder tanzen die Namen ein farbenfrohes Fest und wir tanzten bis in die Morgenstunden“ – Zur praktischen Kultur des Graffiti - Tophinke, Doris (Kommunikative und sprachliche Praktiken)

Science teaching processes - Introduction to strand 3. In Lavonen, J., Juuti, K., Lampiselkä, J., Uitto, A., & Hahl, K. (eds.), Electronic Proceedings of the ESERA 2015 Conference. Science education research: Engaging learners for a sustainable future.

Risk-taking incentives through excess variable compensation: Evidence from European banks - Uhde, André (The Quarterly Review of Economics and Finance)
Employing compensation data provided by 63 banks from 16 European countries for the period from 2000 to 2010 this paper empirically investigates the impact of excess variable compensation on bank risk. As a main finding, we provide evidence for a risk-increasing impact of excess variable pay for both executive variable cash-based and variable equity-based compensation. This baseline finding holds under various robustness checks, in particular when controlling for likely reverse causality between bank risk and variable compensation by employing Granger-causality tests and instrumental variable regressions. In addition, results from a large number of sensitivity analyses including board and banking characteristics as well as the financial crisis period and the quality of a country's regulatory framework provide further important implications for banking regulators and politicians in Europe.
Keywords: Banking; Executive compensation; Risk-taking; Financial stability

Förderschwerpunkte Sozial-Emotionale Entwicklung und Lernen (SEELe): Zusammensetzung der Schülerschaft an Förderschulen und im inklusiven Unterricht – eine Pilotstudie - Laubenstein, Désirée

Leadership Orientation and the recontextualisation of inclusive education: The principal’s role in mainstreaming schools in Rhineland-Palatinate. Symposium mit Köpfer, A., Sturm, T. & Feyerer, E - Scheer, D.; Laubenstein, Désirée; Lindmeier, C.

Students with Special Educational Needs (SEN) in Learning Disabilities (LD) and Emotional and Behavioural Disorders (EBD) in Rhineland-Palatinate: Social Skills, Behavioural Difficulties and Social Status. - Laubenstein, Désirée; Scheer, D.

Low-Power, Ultra-compact, Fully-differential 40Gbps Direct Detection Receiver in 0.25μm Photonic BiCMOS SiGe Technology - Gudyriev, Sergiy; Scheytt, Christoph; Meister, Stefan; Knoll, Dieter; Lischke, Stefan; Zimmermann, Lars; Meuer, Christian (IEEE Group IV Photonics Conference)
Recently electronic-photonic integrated circuits (EPIC) technology platforms became available [1] which allow fabrication of very compact and fast monolithic receivers. However, although the cointegration of electronics and photonics on the same chip allows for novel circuit topologies which could help to improve circuit performance quite often transmitter and receiver circuit design is using more or less conventional approaches. We propose a novel architecture that effectively utilizes the benefits of the EPIC technology such as: very short interconnects between the photodiode and the amplifier, symmetrical and compact photodiode structure with low operating voltages. Our architecture shown in Fig. 1 features fully-differential input stage, automatic biasing of the photodiode, DC coupling between diode and transimpedance amplifier (TIA) and very small footprint.

Recent Advances in Millimeter-Wave-and Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Microelectronics Seminar)

Electronic-Photonic System-On-Chip - Scheytt, Christoph (DFG Rundgespräch:"Disruptive system concepts using electronic-photonic integration)

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Bay-Extended, Distorted Perylene Esters Showing Visible Luminescence after Ultraviolet Excitation: Photophysical and Electrochemical Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Neuba, Adam; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Klassenklima und Rückmeldungen aus der Sicht von Kindern im dritten und vierten Grundschuljahr im Zusammenhang mit ihren Lernprozessen im Leseunterricht - Hoya, Fabian Karl; Hellmich, Frank (Lernprozessbegleitung und adaptives Lernen in der Grundschule)

Soziale Organisation und enzyklopädisches Interesse. Campanellas metaphysische Grundlegung der Sonnenstadt - Hagengruber, Ruth Edith (Politische Utopien der Neuzeit. Thomas Morus, Tommaso Campanella, Francis Bacon)

Emilie du Châtelet, 1706–1749. Transformer of Metaphysics and Scientist - Hagengruber, Ruth Edith (The Mathematical Intelligencer)

Perspektiven der Pädagogik bei Unterstützungsbedarf der emotionalen und sozialen Entwicklung. - Laubenstein, Désirée

Inklusion an Schwerpunktschulen in Rheinland-Pfalz - Laubenstein, Désirée

Ausgewählte Ergebnisse der GeSchwind-Studie (2011-2014) im Rahmen der Veranstaltung ‘Inklusion ist machbar – Forschung und Praxis zu inklusiven Schulen in Rheinland-Pfalz. Ministerium für Soziales, Arbeit, Gesundheit und Demografie. 23.06.2016 - Laubenstein, Désirée; Lindmeier, C.

Ressourcen nutzen – Kultur des Respekts schaffen: Praxisbeispiele und empirische Befunde zur Schule auf dem Weg zur Inklusion, Symposium - Laubenstein, Désirée; Lindmeier, C.; Guthöhrlein, K:; Scheer, D.; Sponholz, D.

Digitale Welt und Gesundheit. eHealth und mHealth – Chancen und Risiken der Digitalisierung im Gesundheitsbereich - Schlegel-Matthies, Kirsten; Gigerenzer, Gerd; Wagner, Gert G.

'I Believe in Nothing If Not in Action:’ African American Humanism and (Embodied) Agency - Hartmann, Alexandra (COPAS)

Konfliktbeilegung - Kamp, Hermann (Handwörterbuch zur deutschen Rechtsgeschichte)

Die Funktionseliten und die Aufstände in den burgundischen Territorien nach dem Tod Karls des Kühnen - Kamp, Hermann („Armer Konrad“ und Tübinger Vertrag im interregionalen Vergleich. Fürst, Funktionseliten und „Gemeiner Mann“ am Beginn der Neuzeit)

Soziologie der Mediation aus historischer Perspektive - Kamp, Hermann (Zeitschrift für Rechtssoziologie)

Politik statt Triumph? Zum Umgang Philipp Augustus‘ mit dem Sieg von Bouvines - Kamp, Hermann (Bouvines 1214 – 2014: Eine Schlacht zwischen Geschichte und Erinnerung. Deutsch-französische Ansätze und Vergleiche)

Focus on Evidence: Schlussfolgerungen für Lehrerbildung und Fremdsprachenunterricht - Hohwiller, Peter (Focus on Evidence – Fremdsprachendidaktik trifft Neurowissenschaften)

Peer teaching in den drei Phasen der Lehrerbildung - Hohwiller, Peter (Sprachen lehren)

Human-Machine Autonomies - Weber, Jutta; Suchman, Lucy (Autonomous Weapon Systems. Law, Ethics, Policy)

Keep Adding. Kill Lists, Drone Warfare and the Politics of Databases - Weber, Jutta (Environment and Planning D. Society and Space. Special Issue on ‚The Politics of the List: Law, Security, Technology‘ (Hg.: Marieke de Goede/Anna Leander/Gavin Sullivan))

ProfiLe-P+ – Professional Competence in Academic Physics Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Fischer, Hans; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst

Ethical Regulations on Robotics in Europe - Weber, Jutta; Nagenborg, Michael; Capurro, Rafael; Pingel, Christoph (Machine Ethics and Robot Ethics)

Direct measurement of wall slip and slip layer thickness of non-Brownian hard-sphere suspensions in rectangular channel flows - Jesinghausen, Steffen; Weiffen, Rene; Schmid, Hans-Joachim (Experiments in Fluids)
Wall slip is a long-known phenomenon in the field of rheology. Nevertheless, the origin and the evolution are not completely clear yet. Regarding suspensions, the effect becomes even more complicated, because different mechanisms like pure slip or slip due to particle migration have to be taken into account. Furthermore, suspensions themselves show many flow anomalies and the isolation of slip is complicated. In order to develop working physical models, further insight is necessary. In this work, we measured experimentally the wall slip velocities of different highly filled suspensions in a rectangular slit die directly with respect to the particle concentration and the particle size. The slip velocities were obtained using a particle image velocimetry (PIV) system. The suspensions consisting of a castor oil–cinnamon oil blend and PMMA particles were matched in terms of refractive indexes to appear transparent. Hereby, possible optical path lengths larger than 15 mm were achieved. The slip velocities were found to be in a quadratic relation to the wall shear stress. Furthermore, the overall flow rate as well as the particle concentration has a direct influence on the slip. Concerning the shear stress, there seem to be two regions of slip with different physical characteristics. Furthermore, we estimated the slip layer thickness directly from the velocity profiles and propose a new interpretation. The PIV technique is used to investigate the viscosity and implicit the concentration profile in the slit die. It is shown that the particle migration process is quite fast.
Keywords: Rheology; Wall Slip; Slip; apparent slip; suspension

Hans Werner Henze - Tumat, Antje (Lexikon der Oper)

Projekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Schürmann, Mirko; Biehler, Rolf; Hochmuth, Reinhard Karl; Schaper, Niclas; Liebendörfer, Michael (Working Paper Studieneingangsphase Perspektiven aus der Begleitforschung zum Qualitätspakt Lehre)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Liebendörfer, Michael; Schürmann, Mirko (Beiträge zum Mathematikunterricht 2016)

Fallbeispiele im Herforder Rechtsbuch im Kontext der Urteilsaufzeichnungen des späten Mittelalters - Wallmeier, Nadine (Textsortenwandel vom 9. bis 19. Jahrhundert. Akten zur internationalen Fachtagung an der Universität Paderborn vom 9.-13.06.2015.)

Jugend als soziales Kampffeld? Die Konstruktion von Jugend und Jugendpolitiken in Europa zwischen wohlfahrtstaatlicher Regulierung und Politiken der Partizipation - Dahmen, Stephan (Jugendpolitiken. Wie geht Gesellschaft mit "ihrer" Jugend um?)

Are international accounting standards more credit relevant than domestic standards? - Florou, Annita; Kosi, Urska; Pope, Peter F (Accounting and Business Research)
We examine whether the credit relevance of financial statements, defined as the ability of accounting numbers to explain credit ratings, is higher after firms are required to report under International Financial Reporting Standards (IFRS). We find an improvement in credit relevance for firms in 17 countries after mandatory IFRS reporting is introduced in 2005; this increase is higher than that reported for a matched sample of US firms. The increase in credit relevance is particularly pronounced for higher risk speculative-grade issuers, where accounting information is predicted to be more important; and for IFRS adopters with large first-time reconciliations, where the impact of IFRS is expected to be greater. These tests provide reassurance that the overall enhancement in estimated credit relevance is driven by accounting changes related to IFRS adoption. Our results suggest that credit rating analysts’ views of economic fundamentals are more closely aligned with IFRS numbers, and that analysts anticipate at least some of the effects of the IFRS transition.
Keywords: IFRS; debt markets; credit ratings; credit relevance

Accounting quality in private firms during the transition to international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska

Suggestions for Vocabulary Focused Reading Lessons for Mainstream Classrooms Addressing Both L1 and L2 Learners - Seifert, Susanne; Kulmhofer, Andrea; Paleczek, Lisa; Schwab, Susanne; Gasteiger-Klicpera, Barbara (Early Childhood Education Journal)
Keywords: Developmental and Educational Psychology; Education

Einsatz der Widerstandserwärmung bei hydraulischen Schneidgeräten zum Trennen von hochfesten Stahlwerkstoffen in Kraftfahrzeugen - Siewers, Bernd
Die zunehmend eingesetzten hochfesten Stähle im Automobilbau können zu schwerwiegenden Problemen bei Verkehrsunfällen führen, da hydraulische Schneidgeräte zur Befreiung von Personen an ihre mechanischen Grenzen geraten. Ein Ansatz zur Behebung dieses Problems kann die Widerstandserwärmung der zu schneidenden Werkstoffe sein. Im Rahmen dieser Dissertation wurde durch Werkstoffuntersuchungen ermittelt, dass die hochfesten Stähle einen starken Abfall der Festigkeit aufweisen, während bei denselben Temperaturen potentielle Schneidwerkstoffe deutlich höhere Festigkeiten besitzen. Das Konzept wurde schließlich in einem Funktionsmuster umgesetzt. Schneidversuche zeigten, dass durch die Widerstandserwärmung ein deutlicher Abfall der erforderlichen Schneidkraft erreicht werden konnte. Insgesamt konnte gezeigt werden, dass die Widerstandserwärmung ein vielversprechendes Konzept darstellt, um hochfeste Karosseriestähle zuverlässig und schnell zu durchtrennen und somit die Befreiung eingeschlossener Fahrzeuginsassen zu gewährleisten.
Keywords: Leichtbau; Hybridsysteme; Werkstoffe

Middlebrow and Gender: 1890-1945

The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy - Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Advanced Materials Interfaces)

Electric potential screening on metal targets submitted to reactive sputtering - Corbella, Carles; Marcak, Adrian; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 1) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

(Cr,Al)N/(Cr,Al)ON Oxy-nitride Coatings deposited by Hybrid dcMS/HPPMS for Plastics Processing Applications - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

Influence of O2 exposure on the interaction between CH4 and amorphous AlYB14 - Hunold, Oliver; Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Music, Denis; Grundmeier, Guido; Schneider, Jochen M. (Applied Surface Science)

Revising secondary electron yields of ion-sputtered metal oxides - Corbella, Carles; Marcak, Adrian; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Journal of Physics D: Applied Physics)

An efficient PE-ALD process for TiO2 thin films employing a new Ti-precursor - Gebhard, M.; Mitschker, F.; Wiesing, M.; Giner, I.; Torun, B.; de los Arcos de Pedro, Maria Teresa; Awakowicz, P.; Grundmeier, G.; Devi, A. (Journal of Materials Chemistry C)
A new Ti-precursor for low-temperature PE-ALD of titanium dioxide thin films as gas barrier layers on polymer substrates.

Combined Electrochemical and Electron Spectroscopic Investigations of the Surface Oxidation of TiAlN HPPMS Hard Coatings - Wiesing, Martin; to Baben, Moritz; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Electrochimica Acta)

Single-Mode Parametric-Down-Conversion States with 50 Photons as a Source for Mesoscopic Quantum Optics - Harder, Georg; Bartley, Tim; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review Letters)

A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor - Mahnken, Rolf; Caylak, Ismail; Dridger, Alex (A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor)
This paper presents a numerical method for solution of a stochastic partial differential equation (SPDE) for a linear elastic body with stochastic coefficients (random variables and/or random fields). To this end the stochastic finite element method (SFEM) is employed, which uses W IENER’S polynomial chaos expansion in order to decompose the coefficients into deterministic and stochastic parts. As a special case, we consider isotropic material behavior with two fluctuating parameters. Computational approaches involving GALERKIN projection are applied to reduce the SPDE into a system of deterministic PDEs. Furthermore, we consider normally distributed random variables, which are assumed to be stochastically independent, and which establish the number of stochastic dimensions. Subsequently, the resulting finite element equation is solved iteratively. Finally, in a representative example for a plate with a ring hole we study the influence of different variances for material parameters on the variances for the finite element results.

Modeling of variant-interaction during bainitic phase transformation - Ehlenbröker, Ulrich; Mahnken, Rolf; Petersmann, M; Antretter, T (IOP Conference Series: Materials Science and Engineering)

Extension of a multi-mechanism model: Hardness-based flow and transformation induced plasticity for austenitization - Cheng, C.; Mahnken, Rolf (International Journal of Solids and Structures)

Macromodelling of Transformation Induced Plasticity combined with Viscoplasticity for Low-Alloy Steels - Schneidt, Andreas; Mahnken, Rolf (steel research international)

Determination of effective properties for CFRP curing coupled to viscoleasticity based on a three-scale framework - Dammann, Christian; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase field and diffusion models for lower bainite transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Two accuracy improvements on nonuniform transformation field analysis for plasticity coupled to softening - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase Ginzburg-Landau/Cahn-Hilliard systems for simulation of lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (Archive of Applied Mechanics)

A three-scale framework for fibre-reinforced-polymer curing part II: Mesoscopic modeling and macroscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

A three-scale framework for fibre-reinforced-polymer curing Part I: Microscopic modeling and mesoscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

An NTFA-based homogenization framework considering softening effects - Ju, X.; Mahnken, Rolf (Mechanics of Materials)

Design of voltage controlled oscillators (VCOs) in D-band and their phase noise measurements using frequency down-conversion - Ali, U.; Bober, M.; Thiede, Andreas (2016 11th European Microwave Integrated Circuits Conference (EuMIC))

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

The International Liquid Crystal Society 1990–2015 - Dunmur, David; Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Comparison of Cost and Complexity for Various 16-QAM Transmitter Structures in Coherent Optical Systems - Al-Bermani, Ali; Noé, Reinhold (NEXT-GENERATION OPTICAL COMMUNICATION: COMPONENTS, SUB-SYSTEMS, AND SYSTEMS V)

Die Welt 'im schönsten Fall' - Umbruchs- und Katastrophenszenarien im Werk Angela Krauß - Morrien, Rita (Umwelt - sozial, kulturell, ökologisch. Zur Darstellung von Zeitgeschichte in deutschsprachiger Gegenwartsliteratur)

Spuren des Dialogs - literatur- und kulturwissenschaftliche Überlegungen zum Thema Dialog. 50 Jahre diplomatische Beziehungen zwischen Deutschland und Israel - Morrien, Rita (Traces of Dialogue. Symposion and exhibition 2015 between Israel/Rishon LeZion and Germany/Münster)

LiNbO3-Based Endless Optical Polarization Control The Photonic Alternative to Coherent Electronics - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Time-resolved Mueller matrix measurement and polarization scrambler characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

LiNbO3-based endless optical polarization control - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

Accelerated Testing of Polarization-Tracking Receiver Using Polarization Scrambler with Peaked Speed Distribution - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (Photonic Networks; 17. ITG-Symposium; Proceedings of)

Catalani, Angelica - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Tetrazzini, Luisa - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Patti, Adelina - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Pasta, Giuditta - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Lind, Jenny - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Gender - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Gar keine Stimme? Wilhelmine Schröder-Devrient, Wagner und das Singen - Grotjahn, Rebecca (Bühnenrollen und Identitätskonzepte – Karrierestrategien von Künstlerinnen im Theater des 19. Jahrhunderts)

Der Wundersmann: Johann Sebastian Bach und die Kantate Wer nur den lieben Gott lässt walten BWV 93 - Grotjahn, Rebecca ("Ei, dem alten Herrn zoll’ ich Achtung gern'." Festschrift für Joachim Veit zum 60. Geburtstag)

Highly functionalized alkenes produced from base-free organocatalytic Wittig reactions: (E)-3-benzylidenepyrrolidine-2,5-dione, (E)-3-benzylidene-1-methylpyrrolidine-2,5-dione and (E)-3-benzylidene-1-tert-butylpyrrolidine-2,5-dione - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section C Structural Chemistry)
The Wittig reaction is a fundamental transformation for the preparation of alkenes from carbonyl compounds and phosphonium ylides. The ylides are prepared prior to the olefination step from the respective phosphonium salts by deprotonation utilizing strong bases. A first free-base catalytic Wittig reaction for the preparation of highly functionalized alkenes was based on tributylphosphane as the catalyst. Subsequently we developed a system employing a phospholene oxide as a pre-catalyst and trimethoxysilane as reducing agent which operates under milder conditions. The title compounds, ( E )-3-benzylidenepyrrolidine-2,5-dione, C 11 H 9 NO 2 , (I), the methylpyrrolidine derivative, C 12 H 11 NO 2 , (II), and the tert- butylpyrrolidine derivative, C 15 H 17 NO 2 , (III), have been synthesized by base-free catalytic Wittig reactions. In the crystal of (I), molecules are linked into centrosymmetric dimers via pairs of N—H...O hydrogen bonds. Furthermore, in the crystal structure of (III), there are two molecules in the asymmetric unit, whereas in (I) and (II), only one molecule is present.
Keywords: Materials Chemistry; Inorganic Chemistry; Physical and Theoretical Chemistry; Condensed Matter Physics

A novel zinc based binary catalytic system for CO2utilization under mild conditions - Desens, Willi; Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Organic Chemistry Frontiers)
A novel zinc based binary catalytic system for the synthesis of cyclic carbonates under mild and solvent-free conditions utilizing CO2as a C1 building block is reported.
Keywords: Organic Chemistry

Novel Base-Free Catalytic Wittig Reaction for the Synthesis of Highly Functionalized Alkenes - Schirmer, Marie-Luis; Adomeit, Sven; Spannenberg, Anke; Werner, Thomas (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Regio- and Stereoselective Synthesis of Dithiocarbonates under Ambient and Solvent-Free Conditions - Diebler, Johannes; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Convergent Activation Concept for CO2Fixation in Carbonates - Desens, Willi; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

Atom economical synthesis of di- and trithiocarbonates by the lithium tert-butoxide catalyzed addition of carbon disulfide to epoxides and thiiranes - Diebler, J.; Spannenberg, A.; Werner, Thomas (Organic and Biomolecular Chemistry)
The lithium tert-butoxide catalyzed addition of CS2 to epoxides and thiiranes under mild conditions is reported. A mechanism has been proposed taking into account the regio- and stereochemical outcome of the reaction.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Cooperative catalyst system for the synthesis of oleochemical cyclic carbonates from CO2and renewables - Tenhumberg, Nils; Büttner, Hendrik; Schäffner, Benjamin; Kruse, Daniela; Blumenstein, Michael; Werner, Thomas (Green Chemistry)
Taking Control!The binary catalyst system composed of MoO3and an organic phoshponium salt [Bu4P]X proved very efficient to produce oleochemical cyclic carbonates from renewables.
Keywords: Pollution; Environmental Chemistry

Alkoxide-Initiated Regioselective Coupling of Carbon Disulfide and Terminal Epoxides for the Synthesis of Strongly Alternating Copolymers - Diebler, Johannes; Komber, Hartmut; Häußler, Liane; Lederer, Albena; Werner, Thomas (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Iron-Based Binary Catalytic System for the Valorization of CO2 into Biobased Cyclic Carbonates - Büttner, Hendrik; Grimmer, Christoph; Steinbauer, Johannes; Werner, Thomas (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Organocatalyzed Synthesis of Oleochemical Carbonates from CO2and Renewables - Büttner, Hendrik; Steinbauer, Johannes; Wulf, Christoph; Dindaroglu, Mehmet; Schmalz, Hans-Günther; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Aufklärung und Imagination in Frankreich (1675-1810) - Anthologie und Analyse.